Biomarkers of liver fibrosis: prospective comparison of multimodal magnetic resonance, serum algorithms and transient elastography. (2nd July 2020) - Forsgren, Mikael F.; Nasr, Patrik; Karlsson, Markus; Dahlström, Nils; Norén, Bengt; Ignatova, Simone; Sinkus, Ralph; Cedersund, Gunnar; Leinhard, Olof Dahlqvist; Ekstedt, Mattias; Kechagias, Stergios; Lundberg, Peter
Abstract: Background and aims: Accurate biomarkers for quantifying liver fibrosis are important for clinical practice and trial end-points. We compared the diagnostic performance of magnetic resonance imaging (MRI), including gadoxetate-enhanced MRI and 31 P-MR spectroscopy, with fibrosis stage and serum fibrosis algorithms in a clinical setting. Also, in a subset of patients, MR- and transient elastography (MRE and TE) was evaluated when available. Methods: Patients were recruited prospectively if they were scheduled to undergo liver biopsy on a clinical indication due to elevated liver enzyme levels without decompensated cirrhosis. Within a month of the clinical work-up, an MR-examination and liver needle biopsy were performed on the same day. Based on late-phase gadoxetate-enhanced MRI, a mathematical model calculated hepatobiliary function (relating to OATP1 and MRP2). The hepatocyte gadoxetate uptake rate ( KHep ) and the normalised liver-to-spleen contrast ratio (LSC_N10) were also calculated. Nine serum fibrosis algorithms were investigated (GUCI, King's Score, APRI, FIB-4, Lok-Index, NIKEI, NASH-CRN regression score, Forns' score, and NAFLD-fibrosis score). Results: The diagnostic performance (AUROC) for identification of significant fibrosis (F2–4) was 0.78, 0.80, 0.69, and 0.78 for MRE, TE, LSC_N10, and GUCI, respectively. For the identification of advanced fibrosis (F3–4), the AUROCs were 0.93, 0.84, 0.81, and 0.82 respectively. Conclusion: MRE and TE were superior for non-invasive identification of significant fibrosis. Serum fibrosis algorithms developed for specific liver diseases are applicable in this cohort of diverse liver diseases aetiologies. Gadoxetate-MRI was sufficiently sensitive to detect the low function losses associated with fibrosis. None was able to efficiently distinguish between stages within the low fibrosis stages. Lay summary: Excessive accumulation of scar tissue, fibrosis, in the liver is an important aspect in chronic liver disease. To replace the invasive needle biopsy, we have explored non-invasive methods to assess liver fibrosis. In our study we found that elastographic methods, which assess the mechanical properties of the liver, are superior in assessing fibrosis in a clinical setting. Of interest from a clinical trial point-of-view, none of the tested methods was sufficiently accurate to distinguish between adjacent moderate fibrosis stages.